Molecular dynamics and Monte Carlo hybrid simulation for fuzzy tungsten nanostructure formation. (15th June 2015) - Ito, A.M.; Takayama, A.; Oda, Y.; Tamura, T.; Kobayashi, R.; Hattori, T.; Ogata, S.; Ohno, N.; Kajita, S.; Yajima, M.; Noiri, Y.; Yoshimoto, Y.; et al.
Abstract: For the purposes of long-term use of tungsten divertor walls, the formation process of the fuzzy tungsten nanostructure induced by exposure to the helium plasma was studied. In the present paper, the fuzzy nanostructure's formation has been successfully reproduced by the new hybrid simulation method in which the deformation of the tungsten material due to pressure of the helium bubbles was simulated by the molecular dynamics and the diffusion of the helium atoms was simulated by the random walk based on the Monte Carlo method. By the simulation results, the surface height of the fuzzy nanostructure increased only when helium retention was under the steady state. It was proven that the growth of the fuzzy nanostructure was brought about by bursting of the helium bubbles. Moreover, we suggest the following key formation mechanisms of the fuzzy nanostructure: (1) lifting in which the surface lifted up by the helium bubble changes into a convexity, (2) bursting by which the region of the helium bubble changes into a concavity, and (3) the difference of the probability of helium retention by which the helium bubbles tend to appear under the concavity. Consequently, the convex-concave surface structure was enhanced and grew to create the fuzzy nanostructure.